Vibration isolation and energy harvesting integrated in a Stewart platform with high static and low dynamic stiffness - Lu, Ze-Qi; Wu, Dao; Ding, Hu; Chen, Li-Qun (Applied Mathematical Modelling, 2021)
An electromagnetic Stewart platform with high static and low dynamic stiffness is explored to reduce the vibration in six degrees of freedom (6-dofs) and simultaneously harvest energy. Each strut in the Stewart platform contains a moving electromagnet suspended between two fixed permanent magnets that are configured so that the magnet spring has both negative stiffness and soft nonlinearity. The use of stiffness nonlinearity improves vibration isolation efficiency. To obtain the frequency-response function for trans-missibility and the power output in the first primary resonance, we apply the harmonic balance method, which is based on rigid-body dynamics and nonlinear elastic theory. The frequency response curves of the 6-dofs have peaks that redshift and bend leftward (toward lower frequencies), and a bubble-shaped resonance curve appears around the first resonance frequency. The numerical simulations support the analytical results. For various mechanical and electrical parameters, the analytical and numerical results both demonstrate that the frequency band of vibration isolation extends to lower frequencies and produces considerable power output. Moreover, the increase in energy harvesting leads to reduced vibration transmissibility under varying some parameters.